The Psychological Situation of Young Women With Abortion - Suryani Suryani; Cesa Septiana Pratiwi; Sri Ratnaningsih (International Journal of Health Science and Technology, 2021)
According to the World Health Organization (WHO), unsafe abortion due to unwanted pregnancy, performed by someone who does not have the skills or does not meet medical standards has an adverse effect on the physical and psychological health of adolescent women. Psychological problems can also occur in adolescent women who have unsafe abortions such as psychological disorders in the form of depression and anxiety. Method: In reviewing the article using the Arksey and O'Malley methods. Overall, the researchers showed that unsafe adolescent abortion practices significantly affected adolescent psychology after having an abortion. The majority of young women experience psychological problems after having had an illegal abortion.